Flare phenomenon in prostate cancer: recent evidence on new drugs and next generation imaging. (February 2021) - Conteduca, Vincenza; Poti, Giulia; Caroli, Paola; Russi, Sabino; Brighi, Nicole; Lolli, Cristian; Schepisi, Giuseppe; Romeo, Antonino; Matteucci, Federica; Paganelli, Giovanni; Marchetti, Paolo; De Giorgi, Ugo
Over the years, an increasing proportion of metastatic prostate cancer patients has been found to experience an initial bone flare phenomenon under both standard therapies (androgen deprivation therapy, chemotherapy, radiotherapy, abiraterone, enzalutamide) and novel agents (immunotherapy, bone-targeting radioisotopes). The underlying biological mechanisms of the flare phenomenon are still elusive and need further clarification, particularly in relation to different types of treatment and their treatment response assessment. Flare phenomenon is often underestimated and, in some cases, can negatively affect clinical outcome. In cases with suspected bone flare, the treatment should be continued for a minimum of 12 more weeks before further decisions about efficacy can be taken. Physicians and patients should be aware of this effect to avoid unwarranted anxiety and inadequate early discontinuation of treatment. This review aims at highlighting new evidence on flare phenomenon arising after the introduction of new drugs extending across the biochemical, radiographic and clinical spectrum of the disease.